Evaluación de la consideración de los indicadores de género en la elaboración de proyectos institucionales - Rodríguez Zambrano, Katherine Lissette (2016)
The research had as objective to evaluate the consideration of genre indicators in the development of institutional projects in the ESPAM MFL. It was realized as not experimental research; bibliographic and descriptive methods were used. The institutional projects of I+D+I where analyzed from the calls of 2012 to 2015. The results showed that there is sufficient epistemological, methodological and legal information as a guide to apply the genre perspective in institutional projects that were analyzed, providing knowledge to achieve equity genre by the institution. However in an interview with Environmental Engineering teachers and several project authors demonstrated that there is little knowledge about genre topic and those who knew about the topic does not use it in their work or projects, possibly by lack of awareness and training in this approach. The knowledge was not evidenced and analysis of genre relations in the development of institutional projects as well as institutional policies of genre approach is not made visible on the projects, only recognized in written language for the distinction of actors in the investigative process. In project management 65% are run by male researchers and 35% by female researchers, based on the epistemological, methodological and legal information a proposal of indicators.